Coenzyme Q10: A Biomarker in the Differential Diagnosis of Parkinsonian Syndromes - Bartošová, Tereza; Klempíř, Jiří; Hansíková, Hana (Antioxidants (Basel, Switzerland), 2023)
Multiple system atrophy (MSA) is generally a sporadic neurodegenerative disease which ranks among atypical Parkinson's syndromes. The main clinical manifestation is a combination of autonomic dysfunction and parkinsonism and/or cerebellar disability. The disease may resemble other Parkinsonian syndromes, such as Parkinson's disease (PD) or progressive supranuclear palsy (PSP), from which MSA could be hardly distinguishable during the first years of progression. Due to the lack of a reliable and easily accessible biomarker, the diagnosis is still based primarily on the clinical picture. Recently, reduced levels of coenzyme Q10 (CoQ10) were described in MSA in various tissues, including the central nervous system. The aim of our study was to verify whether the level of CoQ10 in plasma and lymphocytes could serve as an easily available diagnostic biomarker of MSA. The study reported significantly lower levels of CoQ10 in the lymphocytes of patients with MSA compared to patients with PD and controls. The reduction in CoQ10 levels in lymphocytes correlated with the increasing degree of clinical involvement of patients with MSA. CoQ10 levels in lymphocytes seem to be a potential biomarker of disease progression.
Keywords: multiple system atrophy; lymphocytes; plasma; atypical parkinsonism; coenzyme Q10